Bcl-2 proteins: Unraveling the details of a complex and dynamic network - Stephanie Bleicken; Ana J. Garcia-Saez (Molecular & Cellular Oncology, 2018)
Apoptosis regulation by Bcl-2 proteins is pivotal for mammalians, not only because it is key for development but also because aberrant apoptosis is prerequisite to severe diseases, like cancer. Recently, we quantified interactions within the Bcl-2 protein network in solution and membranes, and addressed membrane recruitment, preference of interaction partners and the consequences for Bax activation and inhibition.